2012
DOI: 10.1590/s1516-35982012001000012
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotics to replace antibiotics for broilers

Abstract: -This study was carried out to evaluate the effect of supplementation of probiotics (Lactobacillus acidophilus, Enterococcus faecium and Bifidubacterium bifidum) and antibiotics (flavomicina and staquinol) on diets for broilers from 1 to 42 days of age, reared in clean (new litter) and challenged (reused litter) environments. A total of 768 one-day-old male broilers of the Cobb 500 strain were distributed in a completely randomized design in a 2 × 4 factorial arrangement (2 litter types × 4 diets), totaling ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
3
7
0
2
Order By: Relevance
“…Therefore, the beneficial effects of a particular probiotic are strictly dependent on characteristics and quantity of microorganism strains used in the probiotic preparation (Tournut, 1998). The result of the current study is in accordance with findings of other reports (Takahashi et al, 2005;Nunes et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the beneficial effects of a particular probiotic are strictly dependent on characteristics and quantity of microorganism strains used in the probiotic preparation (Tournut, 1998). The result of the current study is in accordance with findings of other reports (Takahashi et al, 2005;Nunes et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Azadegan Mehr et al (2014) found no significant differences in carcass traits among a medicinal plant group, a probiotic group, and a control group. Similar results were observed in the study of Nunes et al (2012) with addition of probiotics to broiler diets. Antimicrobial properties of basil essential oil ingredients such as methyl chavicol and α-pinene have been shown in various papers (Sokovic and van Griensven, 2006;Hanif et al, 2011).…”
Section: Carcass Traitssupporting
confidence: 88%
“…The results showed that probiotics did not have any significant effect on performance in different periods. According to Nunes et al (2012), probiotics do not always have positive outcomes in relation to weight gain and feed conversion of poultry; this is due to several variables, such as poultry health, duration of poultry house downtime and environmental contamination levels.…”
Section: Broiler Performancementioning
confidence: 99%
“…Better performance of broilers fed organic acids or their salts was explained by many authors; as nutrient utilization was improved, gut surface was enlarged and potential pathogens were counteracted (Lückstädt and Millor, 2011;Papatsirous and Billinis, 2012;El-Naggar and Abo El-Maaty, 2017). Regarding probiotics, there were similar observations reported by Nunes et al (2012) who stated no statistically beneficial effects of dietary probiotic supplementation on BWG of broilers from 1 to 42 days of age. Whereas, Shabani et al (2012), reported improved FCR of birds up to 42 days of age upon supplementing diets with different types of probiotics.…”
Section: Statistical Analysessupporting
confidence: 84%